2012
DOI: 10.1155/2012/865679
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Depression: Assessing Mediational Effects of Overt Behaviors and Environmental Reward through Daily Diary Monitoring

Abstract: Gender differences in the prevalence of depression are well documented. To further explore the relation between gender and depression, this study used daily diaries to examine gender differences within thirteen behavioral domains and whether differential frequency of overt behaviors and environmental reward mediated the relationship between gender and depression severity. The sample included 82 undergraduate students [66% females; 84% Caucasian; Mean age = 20.2 years]. Overall, females engaged in a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 86 publications
5
30
1
3
Order By: Relevance
“…It can be observed that these values are below the midpoint of the scale (< 3).Anxiety and psychosomatic symptoms were statistically higher in females than in males. This result is supported by some previous studies in Gaza (Abadsa & Thabet, 2012), Turkey (Bayram (Dyrbye, Thomas, & Shanafelt, 2006), U.S.A (Jenkins et al, 2013;Rosenthal & Schreiner, 2000;Ryba & Hopko, 2012). In Palestine, being an Arabic country, females get used to stay close with their mothers almost all the time since childhood.…”
Section: Resultssupporting
confidence: 82%
“…It can be observed that these values are below the midpoint of the scale (< 3).Anxiety and psychosomatic symptoms were statistically higher in females than in males. This result is supported by some previous studies in Gaza (Abadsa & Thabet, 2012), Turkey (Bayram (Dyrbye, Thomas, & Shanafelt, 2006), U.S.A (Jenkins et al, 2013;Rosenthal & Schreiner, 2000;Ryba & Hopko, 2012). In Palestine, being an Arabic country, females get used to stay close with their mothers almost all the time since childhood.…”
Section: Resultssupporting
confidence: 82%
“…Due to reported sex differences in susceptibility to depression with females experiencing the disorder at nearly twice the rates as males (Kessler, 2003; Nolen-Hoeksema, 2001; Ryba & Hopko, 2012), both males and females were assessed. Relevant behavioral responses were observed throughout the chronic unpredictable stress exposure, dry land spatial task and subsequent probe trial.…”
Section: Introductionmentioning
confidence: 99%
“…Schools need to create an atmosphere where all views are respected through antibias training for school staff members (Ryan & Martin, 2000 ). Teachers and other school professionals need information about the complicated concerns of GLBT parents such as custody, daily prejudice, and information about the strengths of families that are not traditional.…”
Section: Cultural/diversity Issues In Parent Involvementmentioning
confidence: 99%
“…Yet another group of researchers found that self-criticism interacted with symptoms of depression to predict decreased grade point averages mostly in boys (Shahar et al, 2006 ). Students who have less skill in obtaining reinforcement in their environments tend to exhibit greater depression (Ryba & Hopko, 2012 ). Also to consider are factors which exacerbate anxiety and depression such as insuffi cient sleep.…”
Section: Risk Factors For Depressive Symptoms and Disorders In Adolesmentioning
confidence: 99%